Ozonation as an alternative to chlorination for soft wheat flours - Chittrakorn, Sasivimon; Earls, Dru; MacRitchie, Finlay (My University, 2014)
High ratio cakes made from ozonated flour attained volumes and other quality characteristics comparable to those from chlorinated flours at 36 min ozonation time. Ozone thus appears to be a viable and more environmentally acceptable alternative to chlorine. Extraction of lipids from flour caused deterioration of cake quality which was not restored by ozonation indicating that lipids were involved in the improving effects of ozonation. Oxidation by ozone led to higher molecular weights of polymeric proteins.
Keywords: Ozonation; Chlorination; Cake volume; Lipids